The factors associated with age related macular degeneration and quality of life of the patients in a tertiary-level ophthalmic center in Kathmandu - Gautam, P; Shrestha, JK; Joshi, SN (Nepalese Journal of Ophthalmology, 2010)
Introduction:Age-related macular degeneration (ARMD) is a leading cause of blindness in the elderly population. Objective:To frame a profile of patients with ARMD and find out the factors associated with it Materials and methods: A cross-sectional study was carried out including a total of 75 patients with ARMD presenting to the out-patient department of a tertiary level ophthalmic center in Kathmandu. The data pertaining to their demography, ocular and systemic history and the findings of clinical examination and laboratory investigations were analyzed. The quality of life was assessed based on their dependability on the others for daily activity. Results: Mean age of presentation of ARMD was 73 years ±7.93. Of the total, 44 were male and 31 female. Smoking was significantly associated with ARMD (p<0.01). 47 of the subjects had a sedentary lifestyle and 28 a non-sedentary lifestyle. Sedentary life style was significantly associated with ARMD (p=0.028). 48 subjects were hypertensive. Systemic hypertension was significantly associated with ARMD (p = 0.015). 45 had dry ARMD, 21 had wet ARMD and 9 of them had a mixed variety. Thirteen out of the 75 study subjects were leading a normal life while 45 of them had some limitation (self-care only) and 17 of them were dependent on the others for their daily activity. The quality of life was not significantly different between dry and wet ARMD (p = 0.40). Conclusion: Sedentary life style, smoking and hypertension are the modifiable factors that are associated with ARMD. A significant number of people with the ARMD have a compromised quality of life. Keywords: ARMD; associated factors; quality of life; macular degeneration DOI: 10.3126/nepjoph.v1i2.3685 Nep J Oph 2009;1(2):114-117